Perancangan Aplikasi Keuangan Restoran Terintegrasi Pada Warung Arya berbasis Akutansi - Junus Sinuraya (Jurnal Teknovasi : Jurnal Teknik dan Inovasi, 2019)
The design of financial applications in this Arya stall is based on huge business opportunities in the stall, therefore this stall wants to expand its business and requires financial applications that can support this business activity. Financial applications in the Aryan stalls made include master data, expenditure transactions, sales transactions, and financial reports that are expected to approach accounting rules such as (income statement, owner's equity statement and balance sheet report), while the process of making this application uses the Visual Study programming language 2010 and Microsoft SQL Server 2008 as its database and design using Data Flow Diagrams (DFD). The results of this study produce applications that can provide report information that is useful for decision makers for the owner of the stall and this financial application can facilitate the processing of data such as sales and expenditure transactions.